Sacubitril/Valsartan for Blood Pressure Lowering in Non‐Dialysis‐Dependent Chronic Kidney Disease Stage 3–5 Patients With Hypertension: A Multicenter Clinical Study - Yu Yan; Xiaomin Li; Juan Cao; Jingyuan Cao; Yao Wang; Liang Wang; Jirong Yu; Lianhua Chen; Min Yang; Xinzhong Huang; Lei Shen; Hong Ding; et al. (The Journal of Clinical Hypertension)
ABSTRACT To assess the effectiveness and safety of Sacubitril/Valsartan in reducing blood pressure in individuals with non‐dialysis‐dependent chronic kidney disease (NDD‐CKD) Stage 3–5 complicated by hypertension. This study was a multicenter retrospective analysis conducted from March 1, 2022 to March 31, 2024, involving adult patients with NDD‐CKD Stage 3–5 and hypertension, who received Sacubitril/Valsartan either as a monotherapy or in addition to current antihypertensive treatments that were insufficient. The main outcomes measured were blood pressure control, changes in blood pressure and laboratory parameters within 8 weeks post‐treatment initiation, and incidence of adverse events. The study included a total of 459 individuals with NDD‐CKD Stage 3–5 and hypertension. At the study endpoint, mean systolic blood pressure, diastolic blood pressure, and pulse pressure were markedly reduced compared to baseline (all p < 0.001). The average blood pressure reductions were 12.17 (4.66, 22.00), 6.00 (0.67, 12.66), and 6.67 (0.08, 14.00) mmHg, respectively. Throughout the study period, 96 patients (20.92%) with NDD‐CKD Stage 3–5 developed worsening renal function, 15 patients (3.27%) developed hyperkalemia, and 49 patients (10.68%) experienced symptomatic hypotension. Overall, there were no significant differences in the changes in serum creatinine, estimated glomerular filtration rate, and serum potassium before and after treatment (p = 0.28, p = 0.91, p = 0.61, respectively). Sacubitril/Valsartan significantly lowers blood pressure in patients with NDD‐CKD Stage 3–5 complicated by hypertension, with good safety profiles. Trial Registration: ClinicalTrials.gov identifier: ChiCTR2400086079